Impact of mid Eocene greenhouse warming on America’s southernmost floras - Damián A. Fernández (Nature Portfolio, 2021)
Reconstructed floras from southernmost South America during the Middle Eocene Climate Optimum show the impact of this warming event on floral diversity. This reconstructed biota reflects a greenhouse world and offers a climatic and ecological deep time scenario of a sub-Antarctic region in the absence of ice.